Directional porous polyimide/polyethylene glycol composite aerogel with enhanced CO2 uptake performance. (May 2023) - Nie, Yihao; Yi, Xibin; Zhao, Xinfu; Yu, Shimo; Zhang, Jing; Liu, Xiaochan; Liu, Sijia; Yuan, Zhipeng; Zhang, Minna
The cost of CO2 separation and energy consumption can be decreased through the use of CO2 adsorption. Due to the electron-rich heteroatoms in its network, polyimide (PI) has a remarkable affinity for CO2 . Polyethylene glycol (PEG) can increase the layer spacing of polymers, so as to change the mass transfer of CO2 in it. Furthermore, the ether bond (-O-) in PEG has good affinity for CO2. In this study, PEG-1000 was introduced into PI aerogel by mild sol-gel method at low temperature, and freeze-drying was used to produce PI/PEG composite aerogels with directional pore structure. The effect of PEG-1000 content and directional pore structure of the PI/PEG composite aerogels on CO2 adsorption performance were further studied. The L-PI/PEG-4 composite aerogel, which contains 4  g PEG and is directionally frozen in liquid nitrogen, has a CO2 adsorption capacity of 16.76 cm 3 /g at 25°C and 1 bar. L-PI/PEG-4 aerogel also exhibits high CO2 /N2 selectivity and adsorption cycle stability.